2022
DOI: 10.1111/jsr.13666
|View full text |Cite
|
Sign up to set email alerts
|

Association between quality of sleep and screen time during the COVID‐19 outbreak among adolescents in the United Arab Emirates

Abstract: Summary The COVID‐19 pandemic had a major impact on people of all ages. Adolescents' exposure to online learning is linked to excessive screen time on digital devices, which leads to poor sleep quality. This study aimed to investigate the association between screen time on different electronic devices and sleep quality among adolescents in the United Arab Emirates. This study was based on a self‐reported questionnaire, which was administered online to school‐aged adolescents (aged 12–19 years). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have suggested a bidirectional relationship between high DST and poor sleep among children and adolescents (Bani‐Issa et al, in press; Kim et al, 2020; Leonard et al, 2021; Magee et al, 2014); however, such evidence in the adult population is scarce. Our study examined the bidirectional association between DST and sleep patterns in a sample of UK general population adults over nearly 7 years of average follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep habits and problems in adolescence during the pandemic and their relationship with mental health have been widely investigated, mainly through self-reported measures, and a first line of evidence highlights a greater risk of sleep problems in adolescents associated with the COVID-19 pandemic [ 125 , 132 , 133 , 134 , 135 , 136 ]. In their meta-analysis on sleep disturbances during the pandemic in the general population, Jahrami and colleagues found that children and adolescents represented the second most affected group after COVID-19 patients, with an overall prevalence of sleep problems of approximately 46% [ 132 ].…”
Section: The Impact Of Covid-19 Outbreak On Sleep and Mental Health I...mentioning
confidence: 99%
“…From another meta-analytic work, the pooled prevalence of sleep disorders among children and adolescents was 42%, with age, educational levels, and female gender correlating with depressive symptoms (pooled prevalence of 31%), which had an increase of prevalence over time [ 137 ]. Several studies from different countries reported a high prevalence of sleep disorders and poor sleep quality in adolescents during the pandemic [ 133 , 134 , 135 , 136 ]. In a large USA sample, adolescents were more likely to exhibit moderate to severe symptoms of depression, anxiety, post-traumatic stress disorder, suicidal ideation or behavior, and sleep problems compared to adults [ 138 ].…”
Section: The Impact Of Covid-19 Outbreak On Sleep and Mental Health I...mentioning
confidence: 99%
See 1 more Smart Citation